2004
DOI: 10.1590/s0103-84782004000300030
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Leptospira spp from dogs, bovine and swine naturally infected

Abstract: Isolamento de Leptospira spp de cães, bovinos e suínos naturalmente infectados ABSTRACT Leptospira isolation allows definitive diagnosis of the infection. Contamination by microorganisms is one of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
11

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 7 publications
2
18
0
11
Order By: Relevance
“…The antibiotics, at the concentrations used in the EMJH medium, were found to be able in inhibiting contaminants but not leptospires. Myers and Varela-Diaz (12) found that subcultures were needed further on into an antibiotic containing medium, for total elimination of surviving contaminants after 24h, differently from what was described by Freitas et al, Turner, and Schönberg et al (6,16,19), that sub cultured after two days.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The antibiotics, at the concentrations used in the EMJH medium, were found to be able in inhibiting contaminants but not leptospires. Myers and Varela-Diaz (12) found that subcultures were needed further on into an antibiotic containing medium, for total elimination of surviving contaminants after 24h, differently from what was described by Freitas et al, Turner, and Schönberg et al (6,16,19), that sub cultured after two days.…”
Section: Resultsmentioning
confidence: 94%
“…Freitas et al (6) described the leptospires isolation of dogs, bovine and swine naturally infected by leptospires. The urine samples from 14 dogs and three bovines and also kidney, liver, ovary and uterus body samples from 36 slaughtered sows with unknown health records were used.…”
Section: Introductionmentioning
confidence: 99%
“…De fato, como o procedimento de tipificação das estirpes isoladas empregado só identificou a espécie das quatro estirpes e o sorogrupo de duas, não foram identificados os sorovares das mesmas, sendo necessário o emprego dos procedimentos clás-sicos para a identificação dos antígenos de superfície de natureza lipopolissacarídica, tais como a prova de absorção cruzada de aglutininas ou conjuntos de anticorpos monoclonais como já foi realizado em diversas localidades do Brasil, identificando em algumas ocasiões sorovares autóctones, só registrados até o presente unicamente no Brasil (SANTA ROSA; SULZER; CASTRO, 1972;VASCONCELLOS et al, 2001;DEL-BEM et al, 2002;MARVULO et al, 2002;CORRÊA et al, 2004;FREITAS et al, 2004;OLIVEIRA et al, 2005;AHMED et al, 2006;FAGUNDES et al, 2008;MIRAGLIA et al, 2008;ZACARIAS et al, 2008).…”
Section: Metodologiaunclassified
“…infectando animais no Brasil, Santa Rosa, Sulzer e Castro (1972) (AHMED et al, 2006;FAGUNDES et al, 2008). Freitas et al (2004) isolaram a estirpe LO-1 da urina de um cão da cidade de Londrina, PR, tipificada como sorogrupo Canicola sorovariedade Canicola (OLIVEIRA et al, 2005;AHMED et al, 2006;FAGUNDES et al, 2008). Delbem et al (2002) isolaram estirpe L04 do fígado de um suíno, tipificada como pertencente ao sorogrupo Canicola sorovariedade Canicola (FREITAS et al, 2004;FAGUNDES et al, 2008).…”
Section: Introductionunclassified
See 1 more Smart Citation